f(x) -X(ao quadrado)-2x+3
Soluções para a tarefa
Respondido por
2
vamos lá...
f(x)=-x²-2x+3
a=-1
b=-2
c=3
Δ=b²-4ac
Δ=(-2)²-4(-1)(3)
Δ=4+12
Δ=16
![x= \frac{-b\pm \sqrt{\Delta} }{2a} =~~ \frac{-(-2)\pm \sqrt{16} }{-2} =~~ \frac{2\pm4}{-2} \\ \\ x'= \frac{2+4}{-2} = \frac{6}{-2} =-3 \\ \\ x"= \frac{2-4}{-2} = \frac{-4}{-2} =+2 x= \frac{-b\pm \sqrt{\Delta} }{2a} =~~ \frac{-(-2)\pm \sqrt{16} }{-2} =~~ \frac{2\pm4}{-2} \\ \\ x'= \frac{2+4}{-2} = \frac{6}{-2} =-3 \\ \\ x"= \frac{2-4}{-2} = \frac{-4}{-2} =+2](https://tex.z-dn.net/?f=x%3D+%5Cfrac%7B-b%5Cpm+%5Csqrt%7B%5CDelta%7D+%7D%7B2a%7D+%3D%7E%7E+%5Cfrac%7B-%28-2%29%5Cpm+%5Csqrt%7B16%7D+%7D%7B-2%7D+%3D%7E%7E+%5Cfrac%7B2%5Cpm4%7D%7B-2%7D++%5C%5C++%5C%5C+x%27%3D+%5Cfrac%7B2%2B4%7D%7B-2%7D+%3D+%5Cfrac%7B6%7D%7B-2%7D+%3D-3+%5C%5C++%5C%5C+x%22%3D+%5Cfrac%7B2-4%7D%7B-2%7D+%3D+%5Cfrac%7B-4%7D%7B-2%7D+%3D%2B2)
f(x)=-x²-2x+3
a=-1
b=-2
c=3
Δ=b²-4ac
Δ=(-2)²-4(-1)(3)
Δ=4+12
Δ=16
kjmaneiro:
não olha que é -4 sobre -2= - com - =+
Respondido por
1
F(x) -x²-2x+3
a=-1
b=-2
c=3
∆=b²-4.a.c
∆=(-2)²-4.(-1).3
∆=4-4.3
∆=4+12
∆=16
x=-b±√16 / 2.a
x= 2±4 / 2.(-1)
x= 2±4 / -2
x'=2+4 / -2
x'=2+4= 6/-2 = -3
x''=2-4 / -2
x''= -2 / -2
x'' = 1
R {x'=-3 x''=1}
a=-1
b=-2
c=3
∆=b²-4.a.c
∆=(-2)²-4.(-1).3
∆=4-4.3
∆=4+12
∆=16
x=-b±√16 / 2.a
x= 2±4 / 2.(-1)
x= 2±4 / -2
x'=2+4 / -2
x'=2+4= 6/-2 = -3
x''=2-4 / -2
x''= -2 / -2
x'' = 1
R {x'=-3 x''=1}
Perguntas interessantes
Matemática,
11 meses atrás
Matemática,
11 meses atrás
Matemática,
11 meses atrás
Ed. Física,
1 ano atrás
História,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás